Prevalence of Specific Types of Kidney Disease in Patients Undergoing Kidney Biopsy: A Single Centre Experience - Kafle, Mukunda Prasad; Shah, Dibya Singh; Shrestha, Shailendra; Sigdel, Mahesh Raj; Raut, Kanak Bahadur (Journal of Advances in Internal Medicine, 2014)
Background and aims: Prevalence of various types of kidney diseases in Nepalese population has largely been unknown. Knowledge of the prevalence of specific type kidney disease in renal patients has important implications in starting the treatment modalities and prognostification of these patients. We tried to find out the various types of kidney diseases in patient population undergoing kidney biopsy at our centre. Methods: We retrospectively analyzed kidney biopsy reports of patients who underwent Kidney Biopsy from 2007 to 2009 in Tribhuvan University Teaching Hospital (TUTH), Kathmandu. Results: Of the 194 kidney biopsy reports analyzed, 100(51.5%) were females and 94(48.5%) males. Most of the patients 75.773% (n=147) were 16-45yrs age (Mean age 33.7years). Biopsy reports showed Lupus Nephritis in 20.6%(n=40), Focal Segmental Glomerulosclerosis (FSGS) in 19.6%(n=38), IgA Nephropathy in 9.8%(n=19), MPGN 9.8%(n=19), Membranous Nephropathy 8.2%(n=16) and Minimal Change Disease (MCD) in 8.2%(n=16) of the population biopsied. Nephrotic syndrome was the commonest clinical indication for kidney biopsy. Conclusion: Our study demonstrated that Lupus Nephritis is the commonest indication for kidney biopsy at our centre. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10695 Journal of Advances in Internal Medicine 2014;03(01):5-10